Creek Indian History : A Historical Narrative of the Genealogy, Traditions and Downfall of the Ispocoga or Creek Indian Tribe of Indians by One of the Tribe, George Stiggins (1788-1845) - Stiggins, George (Book collections on Project MUSE., 1989)
George Stiggins, a Creek Indian half blood living in Alabama, wrote this history more than 150 years ago. Raised in the white culture by his father, an English trader, Stiggins nevertheless lived in close contact with the Creeks because his mother was a full blood of the Natchez tribe, part of the Creek Confederacy. Stiggins writes with firsthand knowledge of the tribes in the central southeast-the Alabamas, Natchez, Abekas, Uchees, and others. He tells of their origins, their towns and chiefs, and their way of life, he traces critical events leading to the Creek War-the battles of.